Drama Therapy - Penner, Evan M.; Garcia, Reina R.; Hallaq, Tom G. (Kansas State University, 2018)
I would love to have someone to work on capturing the creation of an original play done by the Barrier-Free Theatre, which is part of the Drama Therapy Program. Barrier-Free Theatre is an acting troupe of adults with intellectual and developmental disabilities and K-State students. Each year they choose an idea to create a play about and develop it through improvisation. The whole process goes from September through April, but the creation of the play happens in the fall. We end up with the first read through of the play before the end of the fall semester. If that does not seem to be something that is doable, the drama therapy program has a number of projects that we could get permission from families to be documented because the families love what we do for their children. We have an after school drama class for children on the autism spectrum, an after school class for middle-schoolers with autism who make films, and an after school class for high school kids with autism who make films. The high school group has been doing this together for about 5 years (they started in middle school). And if that doesn’t seem to be doable, I have a scholarship of teaching and learning project I’m working on with my Drama Therapy with Special Populations class. I have had an article published about the use of the class to dissolve stigma about people with disabilities in college-aged students and am currently following that up with a quantitative study using the Bogardus scale which identifies how “closely” people would be willing to interact with people with specific conditions (it’s often used for ethnic distance/closeness in terms of stigma and discrimination, but it has been the go-to scale for studying disability, too).
Keywords: Sally Bailey